Beyond prostate, beyond surgery and beyond urology: The “3Bs” of managing non-neurogenic male lower urinary tract symptoms - Qixiang Song; Paul Abrams; Yinghao Sun (Asian Journal of Urology)
Lower urinary tract symptoms (LUTS), consisting storage, voiding and post-micturition symptoms, is a comprehensive definition involving symptoms that may occur due to several causes. Instead of simply focusing on the enlarged prostate, more attention has to be paid to the entire urinary tract as well as multiple system comorbidities. Therefore, prostate surgery alone does not necessarily provide adequate management and cross-disciplinary collaborations are sometimes required. Based on current literature, this paper proposes the “3Bs” concept for managing non-neurogenic male LUTS, namely, “beyond prostate”, “beyond surgery” and “beyond urology”. The clinical application of the “3Bs” enables urologists to carry out integrated, individualized and precise medical care for each non-neurogenic male LUTS patient. Keywords: Male, Lower urinary tract symptoms, Benign prostatic hyperplasia, Benign prostatic obstruction, Detrusor overactivity, Detrusor underactivity, Prostate surgery, Comorbidities